MEKANISME CORPORATE GOVERNANCE DAN KINERJA KEUANGAN PADA PERUSAHAAN YANG MENGALAMI FINANCIAL DISTRESS - Hadi, Selfi Anggraeni Fauziah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test the influence of corporate governance mechanism (InstitutionalOwnership, Managerial Ownership, Board of Directors, and Board of Commissioners), Liquidity, Leverage, andOperating Capacity to the Financial Distress. The result of the research shows that Institutional ownership hasno influence to the financial distress. Managerial ownership has no influence to the financial distress. Board ofDirectors has no influence to the financial distress, Board of Commissioners has negative influence to thefinancial distress, liquidity has no influence to the financial distress, leverage has no influence to the financialdistress, and operating capacity has positive influence to the financial distress.Keywords : Corporate Governance Mechanism, Liquidity, Leverage, Operating Capacity